Development and Psychometric Properties of the Metacognitive Skills Scale among Primary Schools Students in Egypt - Ali, Gamal Mohamed; Haiba, Mohamed Ahmed Ali; Shafey, Ahmad Abd El Moneim Ibrahim El (International Journal of Psychosocial Rehabilitation, 2020)
The current study attempts to examine the structure and psychometric properties of metacognitive skills scale for primary school students in Egypt. The study questions addressed were: What is the factorial structure of the metacognitive skills scale among a sample of primary school students? Is the metacognitive skills scale have appropriate psychometric properties? A total of 120 students from Egypt completed the scale of metacognitive skills, including males (N= 44) and females (N= 76).The students ranged in age from 11.2 to 12.3 with an average age 11.7 and S.D. 0.84. Confirmatory factor analysis (CFA) was used. The results indicate that the structure of metacognitive skills scale is fit and the scale has appropriate psychometric properties.